Laparoscopic Heller Myotomy and Fundoplication in Patients with Chagas' Disease Achalasia and Massively Dilated Esophagus - Pantanali, Carlos A. R.; Herbella, Fernando A. M.; Henry, Maria A. [UNESP]; Mattos Farah, Jose Francisco; Patti, Marco G. (Southeastern Surgical Congress, 2013)
Laparoscopic Heller myotomy and fundoplication is considered today the treatment of choice for achalasia. The optimal treatment for end-stage achalasia with esophageal dilation is still controversial. This multicenter and retrospective study aims to evaluate the outcome of laparoscopic Heller myotomy in patients with a massively dilated esophagus. Eleven patients (mean age, 56 years; 6 men) with massively dilated esophagus (esophageal diameter greater than 10 cm) underwent a laparoscopic Heller myotomy and anterior fundoplication between 2000 and 2009 at three different institutions. Preoperative workup included upper endoscopy, esophagram, and esophageal manometry in all patients. Average follow-up was 31.5 months (range, 3 to 60 months). Two patients (18%) had severe dysphagia, four patients (36%) had mild and occasional dysphagia to solid food, and five patients (45%) were asymptomatic. All patients gained or kept body weight, except for the two patients with severe dysphagia. Of the two patients with severe dysphagia, one underwent esophageal dilatation and the other a laparoscopic esophagectomy. They are both doing well. Heller myotomy relieves dysphagia in the majority of patients even when the esophagus is massively dilated.